Teamwork Moderates the Effect of Transformational Leadership and Service Support Facilities on Responsiveness - Miswidia, Miswidia (Journal of Hospital Management, 2025)
This study is based on the results of initial observations that show that the speed of drug waiting time service is not in accordance with the stipulation. The purpose of this research is to empirically reveal transformational leadership, service support facilities and teamwork on responsiveness. The type of research is included in the quantitative with  a cross sectional study design. The population used is pharmacy workers. The sampling technique uses saturated samples so that 60 pharmacy officers are the respondents. The data collection technique used a questionnaire, and the analysis method used the three box method analysis as well as multiple linear regression and moderate regression. The results of the analysis prove that simultaneously and partially transformational leadership, service support facilities and teamwork have an effect on responsiveness, teamwork strengthens the influence of transformational leadership and service support facilities on responsiveness